Evolution of Whirly1 in the angiosperms: sequence, splicing, and expression in a clade of early transitional mycoheterotrophic orchids - Muti, Rachel M.; Barrett, Craig F.; Sinn, Brandon T. (Frontiers in Plant Science, 2024)
The plastid-targeted transcription factor Whirly1 (WHY1) has been implicated in chloroplast biogenesis, plastid genome stability, and fungal defense response, which together represent characteristics of interest for the study of autotrophic losses across the angiosperms. While gene loss in the plastid and nuclear genomes has been well studied in mycoheterotrophic plants, the evolution of the molecular mechanisms impacting genome stability are completely unknown. Here we characterize the evolution of WHY1 in four early-transitional mycoheterotrophic orchid species in the genus Corallorhiza by synthesizing the results of phylogenetic, transcriptomic, and comparative genomic analyses with WHY1 genomic sequences sampled from 21 orders of angiosperms. We found an increased number of non-canonical WHY1 isoforms assembled from all but the greenest Corallorhiza species, including intron retention in some isoforms. Within Corallorhiza, phylotranscriptomic analyses revealed the presence of tissue-specific differential expression of WHY1 in only the most photosynthetically capable species and a coincident increase in the number of non-canonical WHY1 isoforms assembled from fully mycoheterotrophic species. Gene-and codonlevel tests of WHY1 selective regimes did not infer significant signal of either relaxed selection or episodic diversifying selection in Corallorhiza, but did so for relaxed selection in the late-stage full mycoheterotrophic orchids Epipogium aphyllum and Gastrodia elata. Additionally, nucleotide substitutions that most likely impact the function of WHY1, such as nonsense mutations, were only observed in late-stage mycoheterotrophs. We propose that our findings suggest that splicing and expression changes may precede the selective shifts we inferred for late-stage mycoheterotrophic species, which therefore does not support a primary role for WHY1 in the transition to mycoheterotrophy in the Orchidaceae. Taken together, this study provides the most comprehensive view of WHY1 evolution across the angiosperms to date.